Exploring EFL Teacher's Interventions on Peer Feedback: a Case Study in a Writing Classroom - Andri Suherman (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2018)
This research article aimed to investigate the effect of interventions deployed by teachers in peer feedback in the context of Indonesian EFL writing classrooms. The participants in this case study were 16 Indonesian tertiary-level EFL learners. It explored types of teacher’s interventions on peer feedback, analyzed whether the learners use peer feedback to improve their writing, and explored how the learners appreciate peer feedback. The research methods used were questionnaire, teacher interventions, and interviews. The findings revealed three main points; (1) the teacher’s interventions were mostly on grammatical errors, inappropriate vocabularies, and content structures, (2) facilitated by the teacher’s interventions, more than 50% of the peer feedbacks were integrated by the students in their revision, (3) the students generally confirmed the usefulness of interventions deployed by the teacher on peer feedback. The implications of this study were to provide practical insight to EFL teachers into how peer feedback, supported by teacher interventions, can be develop to benefit learning, and to inform EFL teachers with some suggestions to carry out peer feedback to improve learners’ skill of writings.